Building a Competency based and Professional Human Resources System - Elli Sulistyaningsih (East Asian Journal of Multidisciplinary Research, 2022)
In addition, in the General Pattern of Long Term Development II it is also emphasized that the main objective of national development is to improve the quality of people and the people of Indonesia. In addition to running the wheels of government, residents also manage all natural resources that become wealth for the country concerned. The population of a good quality country will strive to cultivate and utilize existing natural resources, to meet the needs of life and improve their welfare and to manage their country's wealth properly and efficiently. Development of competency based and professional based human resources is conducted in order to deliver results in accordance with organizational goals and objectives with predefined performance standards. Professional human resources are those who have the competence, in accordance with the profession that ditekuni. The objective to be achieved by human resource management is to form professional human resources, which have characteristics, noble, competent, and motivated.